Knowledge boundaries for implementation of quality improvement interventions; a qualitative study - Lyng, Hilda Bø; Strømme, Torunn; Ree, Eline; Johannessen, Terese; Wiig, Siri (Frontiers in Health Services, 2024)
IntroductionImplementation and adoption of quality improvement interventions have proved difficult, even in situations where all participants recognise the relevance and benefits of the intervention. One way to describe difficulties in implementing new quality improvement interventions is to explore different types of knowledge boundaries, more specifically the syntactic, semantic and pragmatic boundaries, influencing the implementation process. As such, this study aims to identify and understand knowledge boundaries for implementation processes in nursing homes and homecare services.MethodsAn exploratory qualitative methodology was used for this study. The empirical data, including individual interviews (n = 10) and focus group interviews (n = 10) with leaders and development nurses, stem from an externally driven leadership intervention and a supplementary tracer project entailing an internally driven intervention. Both implementations took place in Norwegian nursing homes and homecare services. The empirical data was inductively analysed in accordance with grounded theory.ResultsThe findings showed that the syntactic boundary included boundaries like the lack of meeting arenas, and lack of knowledge transfer and continuity in learning. Furthermore, the syntactic boundary was mostly related to the dissemination and training of staff across the organisation. The semantic boundary consisted of boundaries such as ambiguity, lack of perceived impact for practice and lack of appropriate knowledge. This boundary mostly related to uncertainty of the facilitator role. The pragmatic boundary included boundaries related to a lack of ownership, resistance, feeling unsecure, workload, different perspectives and a lack of support and focus, reflecting a change of practices.DiscussionThis study provides potential solutions for traversing different knowledge boundaries and a framework for understanding knowledge boundaries related to the implementation of quality interventions.